Catalyst‐ and Metal‐Free Photo‐Oxidative Coupling of Thiols with BrCCl3. Issue 23 (17th June 2022) - Li, Xiaoman; Fan, Jiali; Cui, Dezhi; Yan, Hui; Shan, Shiquan; Lu, Yongna; Cheng, Xiamin; Loh, Teck‐Peng
Abstract: This paper reported a catalyst‐ and metal‐free method to construct disulfide bond with BrCCl3 under light irradiation. This clean and mild reaction promoted the oxidative coupling of thiols with wide substrate scope, and is applicable to benzylic, aryl and aliphatic thiols, especially cysteine derivative. The disulfides were obtained in high yields up to 98 %, avoiding the use of heating, strong oxidant, metal reagent or catalyst. This facile strategy will facilitate the synthesis of disulfide compounds. Abstract : A photo‐oxidative homo‐coupling of thiol was promoted by BrCCl3 in THF. This catalyst‐ and metal‐free method was used to synthesize disulfides under mild conditions. The clean reaction minimized the possibility of contamination of the product.